Collagen wrapping and local platelet‐rich fibrin do not improve the survival rates of ACL repair with dynamic intraligamentary stabilization: a retrospective case series after ≥5 years postoperatively - Sophie C. Eberlein; Vanessa Rodriguez; Andreas Hecker; Katharina Schürholz; Sufian S. Ahmad; Frank M. Klenke (Journal of Experimental Orthopaedics)
Abstract Purpose Anterior cruciate ligament (ACL) repair has been recommended as a treatment principle for ACL tears. Several authors have advocated a potential role for primary repair techniques in the ACL decision tree. However, long‐term results have been controversial. This study aims to determine the survival of the primarily repaired ACL after dynamic intraligamentary stabilization (DIS) with and without augmentation. Methods Between 2014 and 2019, 102 patients with isolated proximal ACL ruptures underwent DIS repair within 21 days from injury and were available for follow‐up either clinically or telephonically after ≥5 years postoperatively. In 45 cases, DIS repair was augmented with collagen fleece wrapping, platelet‐rich fibrin (PRF) or both. Failure was defined as traumatic re‐rupture or conversion to ACL reconstruction. The patients being available for physical examination underwent a.‐p. stability measurement with a KT‐1000 device. Functional outcome was measured with the IKDC, Tegner and Lysholm scores. Kaplan‐Meier survival analysis, Log‐Rank Test and Binominal logistic regression were performed. Results After a minimum 5‐year follow‐up, 71/102 (69.6%) DIS repairs were not re‐reptured and clinically and/or subjectively stable. Augmentation did not improve survival rates (p = 0.812). The identified factors influencing failure were a younger age and a pre‐injury Tegner activity level of ≥7. 95.7% of those patients with an intact ACL repair had normal or near normal knee function based on the IKDC scoring system. Conclusions The 5‐year overall survival rate of DIS was 69.6%. Collagen fleece wrapping and local PRF application did not improve survival. Patients not suffering failure of repair demonstrated high satisfaction. Nevertheless, the results are inferior to those of established ACL reconstruction procedures. Level of evidence Case series, Level IV.